Measured Catch Blue swimming crab (Portunus pelagicus) Based on the Walter-Hilbron Non-Equilibrium Model) Bangkalan Madura Waters - Siti Naviah; Samsul Huda; Dyah Arini (Universitas Muhammadiyah Malang, 2022)
Blue swimming crab (Portunus pelagicus) as an export product relies mostly on catches, one of which is in Fishery Management Area 712, where this research was carried out. The frequency of fishing efforts continues to increase because of its high economic value; however, there is not much information about the resource as a basis for following up on Law Number 45 of 2009 concerning measurable fish catches based on control output. Descriptive research method with the aim of mapping crab resources based on the